2020
DOI: 10.1111/jsbm.12488
|View full text |Cite
|
Sign up to set email alerts
|

“We Know Their House, Family, and Workplace”: Trust in entrepreneurs’ trade credit relationships in weak institutions

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 66 publications
(73 reference statements)
1
27
0
Order By: Relevance
“…The insights from this study highlight the significance of informal institutions such as personal networks and trust in diaspora entrepreneurship growth in Africa. Thus, the findings support the view that native entrepreneurs can rely on trust, personal networks and cultural proximities to grow firms in weak formal institutions (see Amoako, Akwei and Damoah, 2018;Amoako and Lyon, 2014;Zhu et al, 2011).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The insights from this study highlight the significance of informal institutions such as personal networks and trust in diaspora entrepreneurship growth in Africa. Thus, the findings support the view that native entrepreneurs can rely on trust, personal networks and cultural proximities to grow firms in weak formal institutions (see Amoako, Akwei and Damoah, 2018;Amoako and Lyon, 2014;Zhu et al, 2011).…”
Section: Discussionsupporting
confidence: 75%
“…Much research on entrepreneurship has drawn from economic (North, 1990) and sociological (Scott, 2001) perspectives on institutions to explain how resource allocations, formal structures and socio-cultural norms interact to shape enterprise formation and development in different contexts (see Amankwah-Amoah, 2016;Amoako, Akwei and Damoah, 2018;Brinkerhoff, 2016;Bruton, Ahlstrom and Li, 2010;Hardy et al, 2014;Parker, 2010;Peng et al, 2008;Peng et al, 2009;Zoogah et al, 2015). Diaspora entrepreneurship scholars have also followed suit to appropriate economic and social dimensions of institutions to understand migrant entrepreneurs' institutional challenges and prospects in their countries of residence (Riddle and Brinkerhoff, 2011;Sepulveda et al, 2011;Syrett and Sepulveda, 2012) and countries of origin (see Brinkerhoff, 2016;Coniglio and Brzozowski, 2016;Nkongolo-Bakenda and Chrysostome, 2013;Ojo, Nwankwo and Gbadamosi, 2013) and how these implicate on their business resources and their successes or failures.…”
Section: Institutions and Diaspora Entrepreneurship In Emerging Economiesmentioning
confidence: 99%
“…However, extreme customer orientations are known to inhibit the breakthrough of innovations that create markets and disrupt equilibrium since these radical changes occur in front of customers (Becherer et al, 2008). Access to markets is often associated with an increase in trading (Amoako et al, 2020;Dana et al, 2007;Paul & Boden, 2011;Pergelova et al, 2019). Consistent with that, Lincoln (2012) found that the market might record little or no influence on business growth in terms of sales and turnover in unfavorable economic conditions, especially in women-owned enterprises, despite the significant role markets are conceptualized to have in much of the entreprenuerial ecosystem literature (cf., Isenberg, 2010;Liguori et al, 2019).…”
Section: Marketmentioning
confidence: 75%
“…In the absence of established government institutions, traders involved in export business in the African context have resorted to informal institutions including export trade associations and indigenous institutions (Amaoko, 2015;Amoako et al, 2020;Smith and Luttrel, 1994) for support. Within these rarely studied establishments, trade agreements and contracts are mainly legislated on the basis the of personal trust (Omeihe, 2019).…”
Section: Trust and Export Behaviour In Informal Institutionsmentioning
confidence: 99%